Characterization of Synthesized Polymeric Blend Membranes Enhanced By Methyl Diethanolamine For Efficient co2Separation - Mushtaq, A. (Yildiz Technical University, 2021)
The limited performance of pure glassy and rubbery polymeric membranes for natural gas purification are due to their intrinsic properties. Optimizing their properties by blending both polymers are expected to address the shortage. The foremost objective of this research is to synthesis enhance polymer blend membranes (EPBM) using glassy polysulfone (PSU) and rubbery polyvinyl acetate (PVAc) with the addition of amine for carbon dioxide (CO2) removal from methane (CH4). The EPBM were developed by varying the composition of PVAc ranging from 5 to 20 wt. with 95 to 80 wt. base PSU in dimethylacetamide (DMAc) solvent. The amines composition was added to the blend and kept at 10 wt. over solvent. The findings showed good miscibility between PSU and PVAc blends and the original functional groups of polymers and amines were shown by FTIR with very few spectral peak shifts. The synthesized EPBM were found to have homogenous surfaces and a packed bed sphere structure as shown by FESEM images. Increasing the composition of PVAc from 5 to 20 wt. has significantly reduced the glass transition temperature (Tg) of PSU from 185.09oC to 155.75oC. Â© 2021. All Rights Reserved.